Efforts to catalogue non-governmental organizations with a role in global burn relief. Issue 4 (June 2020) - Fabia, Renata; Gallagher, James; Wheeler, Krista K.; Johnson, Morgan; Cadelski, Karol; Armstrong, Megan; Pilato, Tara; Heffernan, Jamie; Thakkar, Rajan K.; Sales, Stephen; Giles, Sheila; Jeng, James C.
Highlights: Non-governmental organizations (NGOs) play key roles in global burn relief. Collaboration is needed to comprehensively catalogue NGO burn relief activities. World Health Organization Emergency Medical Teams coordinate disaster response. Abstract: Introduction: Non-governmental organizations (NGOs) have been instrumental in the treatment of traumatic injuries, including burns, particularly in low- and middle-income counties. The purpose of this project was to catalogue burn injury related NGO activities, describe coordinated efforts, and provide insight to burn health care professionals seeking volunteer opportunities. Methods: Eligible burn NGOs were identified through internet searches, literature reviews, and social media. The organizations' websites were reviewed for eligibility and contact was attempted to confirm details. Global health organizations, including the World Health Organization, were consulted for their viewpoints. Results: We identified 27 unique NGOs working in the area of burn care in African countries, all with differing missions, capacities, recruitment methods, and ability to respond to disaster. We also describe 14 global NGOs, some of which accept volunteers. Some NGOs were local, while others were headquartered in western countries. Conclusions: To our knowledge, this is the first effort towards the establishment of a Burn-NGO catalogue. Challenges included: frequent shifts in geographical regions supported, lack of collaboration among organizations, availability of public information, and austere environments. We invite collaborators to assist in the creation of a comprehensive, interactive and complete catalogue.